2022
DOI: 10.3389/fped.2022.865099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Severe Viral Pneumonia Caused by SARS-CoV-2 and Other Respiratory Viruses Among Malaysian Children During the COVID-19 Pandemic

Abstract: ObjectivesWe described the etiology of severe pneumonia in children during the height of the COVID-19 pandemic in Malaysia and compared the clinical features of severe SARS-CoV-2 to other respiratory viruses.MethodsThis retrospective study included all children aged 12 years and below hospitalized with severe pneumonia in Negeri Sembilan, Malaysia, between 1 April 2021 and 31 October 2021. We extracted demographic and clinical data and used logistic regression to examine risk factors associated with severe SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…However, our ratio of males to females was almost similar to published studies regionally 23,24 . The predominance of Malays in our patient cohort was consistent with the demographic distribution of COVID‐19 in our earlier publications 21,25,26 . The majority of patients in our study demonstrated seropositivity for SARS‐CoV‐2 antibodies, as opposed to direct detection of the virus through RT‐PCR, suggesting MIS‐C as a post‐infectious phenomenon 27 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, our ratio of males to females was almost similar to published studies regionally 23,24 . The predominance of Malays in our patient cohort was consistent with the demographic distribution of COVID‐19 in our earlier publications 21,25,26 . The majority of patients in our study demonstrated seropositivity for SARS‐CoV‐2 antibodies, as opposed to direct detection of the virus through RT‐PCR, suggesting MIS‐C as a post‐infectious phenomenon 27 …”
Section: Discussionsupporting
confidence: 90%
“…23,24 The predominance of Malays in our patient cohort was consistent with the demographic distribution of COVID-19 in our earlier publications. 21,25,26 The majority of patients in our study demonstrated seropositivity for SARS-CoV-2 antibodies, as opposed to direct detection of the virus through RT-PCR, suggesting MIS-C as a post-infectious phenomenon. 27 The clinical presentation of MIS-C was diverse, characterized by fever and multi-system involvement, particularly the gastrointestinal, mucocutaneous, and cardiovascular systems.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Hence, other viral or bacterial co‐infection causing serious disease could have been missed. However, the negative blood cultures for all patients who were started on iv antibiotics and the low co‐detection rates of other respiratory viruses, as demonstrated in our previous study, 23 suggest that the severity of the disease was caused by SARS‐CoV‐2 alone. Fourth, genomic sequencing for SARS‐Cov‐2 variants was not performed in this study.…”
Section: Discussionsupporting
confidence: 48%
“…Duration of illness was calculated from the first symptom onset. A potential source of infection with an adult or child was specified based on the age and nature of contact, as defined previously 10 . When multiple family members were symptomatic, the first family member who became symptomatic was regarded as the sick contact.…”
Section: Methodsmentioning
confidence: 99%